The Roles of Personality Dimensions and Attachment Styles on Working Mothers’ Psychological Distress During the COVID-19 Pandemic: [Peran Dimensi Kepribadian dan Attachment Styles Terhadap Psychological Distress Selama Pandemi COVID-19 Pada Ibu Bekerja] - Kaswang, Febrika; Halim, Magdalena S. (Faculty of Psychology, Universitas Surabaya, 2024)
The COVID-19 pandemic situation causes psychological distress for working mothers. Personality and attachment styles are protective factors against psychological distress. The purpose of this study was to determine the relationship between personality dimensions and types of attachment styles with psychological distress level. This study also aims to find the predictors of psychological distress. The measuring instruments are the Big Five Inventory (BFI), Attachment Styles Questionnaire (ASQ), and the Kessler Psychological Distress Scale (K10). The three measuring instruments were administered to 297 women aged 26-39 years old, who were working from home, and had children aged 1-5 years. Participants were obtained using convenience sampling and the data collection process took place online. Data analysis utilized Spearman’s correlation to test the correlation between variables and multiple regression to test predictor regression of each variable. The results showed positive relationship on the dimension of neuroticism, type of discomfort, type of relationships, type of approval, and type of preoccupation with psychological distress level. The dimension of extraversion, agreeableness, conscientiousness, and the type of confidence showed a negative relationship, while the dimension of openness did not show any relation. The results of the regression test showed three aspects that act as predictors, namely the dimension of neuroticism, type of approval, and type of preoccupation. The dimension of neuroticism was the predictor with highest contribution. Based on these results, it can be concluded that personality dimensions contribute more dominantly to psychological distress than types of attachment styles. Situasi pandemi COVID-19 menimbulkan psychological distress pada ibu bekerja. Kepribadian dan attachment styles dapat menjadi faktor protektif terhadap psychological distress. Tujuan studi ini adalah mengetahui hubungan antara dimensi kepribadian dan tipe attachment styles dengan tingkat psychological distress. Selain itu, studi ini juga ingin mencari prediktor psychological distress. Alat ukur yang digunakan adalah Big Five Inventory (BFI), Attachment Styles Questionnaire (ASQ), dan Kessler Psychological Distress Scale (K10). Alat ukur diadministrasikan kepada 297 perempuan berusia 26-39 tahun, yang melakukan work from home (WFH), dan memiliki anak berusia 1-5 tahun. Partisipan diperoleh dengan convenience sampling dan proses pengambilan data berlangsung secara daring. Analisis data menggunakan Spearman’s correlation untuk uji korelasi antar variabel dan multiple regression untuk uji prediktor tiap variabel. Hasil studi menunjukkan hubungan positif pada dimensi neuroticism, tipe discomfort, tipe relationships, tipe approval, dan tipe preoccupation terhadap tingkat psychological distress. Dimensi extraversion, agreeableness, conscientiousness, dan tipe confidence menunjukkan hubungan negative, sementara dimensi openness tidak menunjukkan hubungan. Hasil uji regresi menunjukkan tiga aspek yang berperan sebagai prediktor, yaitu dimensi neuroticism, tipe approval, dan tipe preoccupation. Dimensi neuroticism merupakan prediktor dengan kontribusi terbesar. Berdasarkan hasil tersebut, dapat disimpulkan bahwa dimensi kepribadian berkontribusi lebih dominan terhadap psychological distress daripada tipe attachment styles.